Neuropsychological development of children with biliary atresia after liver transplantation - A. V. Syrkina; I. E. Pashkova; A. R. Monakhov; O. V. Silina; E. V. Chekletsova; S. Yu. Oleshkevich; I. B. Komarova; O. M. Tsirulnikova (Вестник трансплантологии и искусственных органов, 2021)
Background. In young children, the most common liver disease leading to transplantation is biliary atresia. Liver transplantation has fundamentally improved the survival rate of children with biliary atresia. Studies on developmental outcomes in children are mostly limited to small samples; there are no such studies in the Russian Federation.Objective: to determine the cognitive outcomes in children undergoing one-stage or two-stage surgical treatment of biliary atresia.Materials and Methods. 83 children were divided into groups: 36 children underwent transplantation without previous surgical interventions (group 1), 47 children underwent the Kasai palliative portoenterostomy (group 2). Inclusion criteria: 24 months of age or younger at the moment of transplantation, no medical history of neurological pathology. All children were examined before transplantation and at 1, 3, 6 and 12 months after liver transplantation. Psychomotor development was assessed using the Griffiths Psychomotor Development Scale for children under 24 months (translated by E.S. Keshishian), the Griffiths Intellectual Development Scale for children aged 2 to 8 years, and the Modified Checklist for Autism in Toddlers, Revised, for children 16-30 months old.Results. All children had developmental delays at the time of transplantation. Up to 50% of the children had signs of cachexia, with a shoulder circumference of less than 3 percentile. Only two children showed obvious hepatic encephalopathy in the form of depressed consciousness. After liver transplantation, 94% of group 1 children recovered their preoperative psychomotor development levels, and only 68% in group 2 made these gains. At 3 and 6 months after transplantation, about 80% of group 1 children showed normal psychomotor development, whereas in group 2, only 61% did. By 12 months after liver transplantation, the difference between the groups was more evident: 83.3% of group 1 children and only 53.2% of group 2 children were developing according to age. The difference between the groups was statistically significant (p < 0.05).Conclusion. Children who received one-stage treatment of biliary atresia and underwent liver transplantation have better neuropsychological development within a year after surgery than children with two-stage surgical treatment.